2013
DOI: 10.5897/jssem12.058
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Uranium in contaminated water samples of Bathinda, Punjab by Desulfovibrio genus

Abstract: Soluble uranium salts enter human body through ground water and foodstuff. World Health Organization (2004) has set 15 µg/L as the "tolerated intake" of soluble uranium in drinking water. Uranium intake above this concentration is toxic to human body. The organ which are most affected are kidney and lungs leading to malfunctioning of kidneys and lung cancer. Soluble uranium is also known for its neuro-developmental, neuropsychological, cytotoxic, genotoxic and carcinogenic effects. So to overcome such hazardou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Uranium is a naturally occurring radioactive heavy metal that can cause many adverse effects on animals and human health, , such as nephrotoxicity, genotoxicity and developmental defects. In certain regions of New Mexico, Australia, Austria, Kazakhstan, Canada, India, and the Czech Republic, where uranium abundantly exists in the bedrocks and groundwater, local civilians can suffer high elevations of uranium in their blood through contaminated water sources. , In addition, the potential of radioactive discharge from nuclear plants during meltdowns can also pose long-term water hazards. According to the US EPA (Environment Protection Agency) guideline, the maximum contamination limit of uranium is 30 μg/L, based on the long-term intake of the material in every day water intake of 2 L for 70 years. The major reasons for its presence in the environment, besides the leaching from bedrocks and emission from nuclear plants, also includes coal combustion and fertilizer use containing uranium traces, which can all cause groundwater contamination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uranium is a naturally occurring radioactive heavy metal that can cause many adverse effects on animals and human health, , such as nephrotoxicity, genotoxicity and developmental defects. In certain regions of New Mexico, Australia, Austria, Kazakhstan, Canada, India, and the Czech Republic, where uranium abundantly exists in the bedrocks and groundwater, local civilians can suffer high elevations of uranium in their blood through contaminated water sources. , In addition, the potential of radioactive discharge from nuclear plants during meltdowns can also pose long-term water hazards. According to the US EPA (Environment Protection Agency) guideline, the maximum contamination limit of uranium is 30 μg/L, based on the long-term intake of the material in every day water intake of 2 L for 70 years. The major reasons for its presence in the environment, besides the leaching from bedrocks and emission from nuclear plants, also includes coal combustion and fertilizer use containing uranium traces, which can all cause groundwater contamination.…”
Section: Introductionmentioning
confidence: 99%
“…3−5 In certain regions of New Mexico, Australia, Austria, Kazakhstan, Canada, India, and the Czech Republic, where uranium abundantly exists in the bedrocks and groundwater, 6 local civilians can suffer high elevations of uranium in their blood through contaminated water sources. 7,8 In addition, the potential of radioactive discharge from nuclear plants during meltdowns can also pose long-term water hazards. 7−9 According to the US EPA (Environment Protection Agency) guideline, the maximum contamination limit of uranium is 30 μg/L, 10 based on the long-term intake of the material in every day water intake of 2 L for 70 years.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first ones can conserve energy for their anaerobic growth through the reduction of uranium, while the SRB are unable to conserve such energy for their growth. Desulfovibrio has been found in different uranium-contaminated sites such as sub-surface sediments ( Castañeda-Carrión et al, 2010 ; Newsome et al, 2014 ), and water ( Parihar et al, 2013 ; Jroundi et al, 2020 ). Povedano-Priego et al (2022) identified Desulfovibrio in the bacterial community of uranium-treated bentonite under anoxic conditions in presence of glycerol-2-phosphate (G2P).…”
Section: Interaction Mechanisms Between Microorganisms and Relevant R...mentioning
confidence: 99%